1998
DOI: 10.1002/(sici)1098-2264(199812)23:4<350::aid-gcc10>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

The expression pattern of the Hmgic gene during development

Abstract: The technique of RNA in situ hybridization to mouse embryo sections from different developmental stages was used to perform a detailed analysis of the expression pattern of the gene for the architectural chromatin factor Hmgic. At early stages of fetal development (day 9.5 post conceptionem), Hmgic is expressed at a high rate throughout the whole embryo. In the second half of development, the pattern of expression becomes more restricted. Expression is found in mesenchymal derivatives, which differentiate into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 15 publications
3
52
1
Order By: Relevance
“…High-mobility group A2 expression has been shown to be undetectable or to remain at low levels in normal adult tissues (Manfioletti et al, 1991;Zhou et al, 1995;Rogalla et al, 1996;Rommel et al, 1997;Hirning-Folz et al, 1998;Gattas et al, 1999). In the present study, however, a highly sensitive RT -PCR analysis revealed the expression of the HMGA2 gene in non-neoplastic pancreatic tissue, although its expression level was significantly lower than that in carcinoma.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…High-mobility group A2 expression has been shown to be undetectable or to remain at low levels in normal adult tissues (Manfioletti et al, 1991;Zhou et al, 1995;Rogalla et al, 1996;Rommel et al, 1997;Hirning-Folz et al, 1998;Gattas et al, 1999). In the present study, however, a highly sensitive RT -PCR analysis revealed the expression of the HMGA2 gene in non-neoplastic pancreatic tissue, although its expression level was significantly lower than that in carcinoma.…”
Section: Discussioncontrasting
confidence: 52%
“…High-mobility group A2 has been shown to be expressed abundantly during embryogenesis, but its expression is either undetectable or remains at low levels in other normal adult tissues (Manfioletti et al, 1991;Zhou et al, 1995;Rogalla et al, 1996;Rommel et al, 1997;Hirning-Folz et al, 1998), suggesting that HMGA2 plays an important role (or roles) in cell proliferation and/ or differentiation. Consistent with this, it has been demonstrated that HMGA proteins are phosphorylated in a cell-cycle-dependent manner (Reeves et al, 1991).…”
mentioning
confidence: 99%
“…10). Like IMP2, HMGA2 is an oncofetal protein: it is expressed at high levels during embryonic development (11,12), whereas it is hardly detectable in adult tissues (13). In many tumor types, the HMGA2 gene is disrupted or aberrantly expressed, making this gene probably the most frequently rearranged gene in human neoplasias (reviewed in refs.…”
Section: Introductionmentioning
confidence: 99%
“…HMGI-C and HMGI(Y) are members of the HMGI family of "highmobility group" (HMG) proteins. They act as architectural transcription factors and are commonly expressed in embryonal cells Hirning-Folz et al, 1998), in transformed cells with a malignant phenotype Bussemakers et al, 1991;Giancotti et al, 1987;1989;Ram et al, 1993), and in a variety of human cancers (Bandiera et al, 1998;Chiappetta et al, 1995;1998;Fedele et al, 1996;Rogalla et al, 1997;Rommel et al, 1997;Tamimi et al, 1993). HMGI-C and HMGI(Y) genes are located at 12q15 and 6p21 (Friedmann et al, 1993), respectively.…”
mentioning
confidence: 99%